An Atypical Biography Concluding More Than Twenty Years of Decroly Research - Depaepe, Marc; Simon, Frank; Van Gorp, Angelo (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
This article provides, at the request of the editors of this journal, an English-language summary of a biography recently published in French about the Belgian educational pioneer Ovide Decroly, on whom we have already published a number of studies: Ovide Decroly (1871-1932): une approche atypique? (Theory and History of Education International Research Group, housed at the Faculty of Education, Queen’s University, Kingston, Ontario, Canada, 2022), 299 pp. (Theory and History of Education Monograph Series, vol. 4). Of that work (Depaepe, Simon & Van Gorp, 2022), which represents the conclusion of more than 20 years of research by the authors on this eminent figure in the Belgian history of education, we outline here briefly the background, methodological starting points, and contents.